2004
DOI: 10.1152/ajpcell.00028.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intracellular superoxide formation in endothelial cells and intact tissues using dihydroethidium and an HPLC-based assay

Abstract: . Detection of intracellular superoxide formation in endothelial cells and intact tissues using dihydroethidium and an HPLC-based assay. Am J Physiol Cell Physiol 287: C895-C902, 2004. First published August 11, 2004 10.1152 10. /ajpcell.00028.2004 was demonstrated that superoxide oxidizes dihydroethidium to a specific fluorescent product (oxyethidium) that differs from ethidium by the presence of an additional oxygen atom in its molecular structure (Zhao H, Kalivendi S, Zhang H, Joseph J, Nithipatikom K, Vá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
202
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(210 citation statements)
references
References 26 publications
3
202
0
5
Order By: Relevance
“…Except for a few studies [2,5] the formation of the characteristic marker product of superoxide/HE reaction, 2-OH-E + , was not investigated. As compared to 2-hydroxyethidium, ethidium was always detected in much higher amounts in these studies [2,5]. Thus, the "red fluorescence" generated from HE in cells is mostly due to ethidium in nearly all of these studies.…”
Section: Ros Detection By Fluorescence Microscopy and Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Except for a few studies [2,5] the formation of the characteristic marker product of superoxide/HE reaction, 2-OH-E + , was not investigated. As compared to 2-hydroxyethidium, ethidium was always detected in much higher amounts in these studies [2,5]. Thus, the "red fluorescence" generated from HE in cells is mostly due to ethidium in nearly all of these studies.…”
Section: Ros Detection By Fluorescence Microscopy and Flow Cytometrymentioning
confidence: 99%
“…Although subtle differences in the spectroscopic properties between E + and 2-OH-E + were used to selectively detect 2-OH-E + and E + in cells under well-defined conditions [4], the fluorescence techniques were largely deemed to be unsuitable for superoxide measurements in cells [2,5]. Using the HPLC-fluorescence method, it was previously shown that the increase in intracellular "red fluorescence" arising from HE could not be solely attributed to 2-OH-E + , as E + was also formed intracellularly from HE during oxidation [2,5]. However, the mechanism of E + formation in cells remained unclear, although E + could be formed from photosensitized oxidation of HE in superoxide-dependent manner [6].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the effects of omega-3 polyunsaturated fatty acids on skeletal muscle cells, we determined superoxide production using the dihydroethidium (DHE) oxidation method (Fink et al 2004;Zhao et al 2003). After 24 h of treatment with 100 μM EPA or DHA freshly prepared before each assay (described above), cells were incubated with 1 μM DHE in DPBS containing 5 mM glucose, for 30 min, at 37°C.…”
Section: Evaluation Of Ros Productionmentioning
confidence: 99%
“…Algunos de estos productos secundarios son el etileno y etanol (relativamente inocuos) y otros pueden ser aldehídos como el malondialdehído (MDA) o hidroxialquenales como el hidroxi-2-nonenal (HNE) que son citotóxicos, alteran la función celular y pueden ser mutagénicos (Dumet y Benson, 2000;. El MDA reacciona con las bases del ADN, especialmente guanina, provocando lesiones mutagénicas y el HNE inhibe el crecimiento celular y es genotóxico (Dizdaroglu, 1992;Cadet et al 1999 (Fink et al 2004) y el diacetato 4,5-diaminofluorescina (DAF-2DA), para detectar la presencia de NO Kojima et al 1998). …”
Section: La Amplificación Arbitraria Del Adn Polimórfico O Rapd (Randunclassified
“…•-y NO, respectivamente, dentro de los tejidos observándolos bajo Microscopio Láser Confocal espectral (CLSM; Rodríguez-Serrano et al 2006;Fink et al 2004;Kojima et al 1998). DCF-DA es un compuesto no fluorescente que es capaz de atravesar las membranas biológicas, y una vez dentro de la célula los grupos acetato son hidrolizados por esterasas intracelulares, convirtiéndose así en un compuesto fluorescente capaz de reaccionar con el H2O2 (Brul et al 1997).…”
Section: Acknowledgementsunclassified